2021
DOI: 10.3390/su13041842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Farm Households’ Vulnerability to Multidimensional Poverty in Rural China

Abstract: The COVID−19 pandemic has significantly impacted the economy and livelihoods of people worldwide. To analyze the impact of the pandemic on material conditions, income levels, health conditions, industrial development and employment opportunities of farmers in China’s rural areas, especially poor areas and explore whether farmers can achieve stable poverty eradication during the COVID−19 pandemic, we interviewed 2662 farm households in poverty−stricken areas of China and used the multidimensional poverty measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
3
15
0
1
Order By: Relevance
“…The results showed that for economic vulnerability, the rural poverty was the most important cause of vulnerability of the studied rural households. This finding was consistent with studies ( 72 ). For the analysis of this finding, it can be said that poverty has plagued the world for a long time and has been one of the main concerns of the development of human societies ( 73 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results showed that for economic vulnerability, the rural poverty was the most important cause of vulnerability of the studied rural households. This finding was consistent with studies ( 72 ). For the analysis of this finding, it can be said that poverty has plagued the world for a long time and has been one of the main concerns of the development of human societies ( 73 ).…”
Section: Discussionsupporting
confidence: 94%
“…For the analysis of this finding, it can be said that poverty has plagued the world for a long time and has been one of the main concerns of the development of human societies ( 73 ). COVID-19 pandemic in 2020 has had a very great effect on the global socio-economic development, and achieving objectives of the United Nations Sustainable Development in 2030, which is the eradication of poverty, has been difficult for many countries, especially third world countries ( 72 ). During COVID-19 pandemic, poverty has become much more than before the disease, for example, a study in China showed that during the disease, poverty among households increased by 27.9% ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et all. [114] present the idea that different state institutions should collaborate to introduce preferential policies and encourage farmers to innovate and start to research their own businesses to drive their motivations. Respondents agree that educating the local population to start entrepreneurial initiatives would mean economic sustainability of the village (Table 17).…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…Second, we use multidimensional poverty, whose reduction has become an important policy objective for governments in developing countries, including Colombia. Third, there is a growing amount of literature using FGLS methodology to study vulnerability in recent years (see for example Liu et al ( 2021 ) and Tigre ( 2019 )).…”
Section: Empirical Strategymentioning
confidence: 99%